Stock price reaction of merger and acquisition (M&A) announcement on Malaysian public listed firms / Nur Shazwani Shamshuddin - Shamshuddin, Nur Shazwani (2013)
The main purpose of this study is to investigate the stock price reaction of merger and acquisition (M&A) announcement based on the Malaysian Public Listed Firms. The study mainly focuses on stock price reaction on the Malaysian public listed firms from 2005 to 2010. The data of a sample of 50 Malaysian public listed firms from a population of 820 public listed firms are collected monthly basis from January 2005 to December 2010. The independent variable that proposed for this study is M&A announcement and the dependent variable is stock price reaction. The analysis that used in this study is event study methodology. The event study period is before the announcement date of M&A (-30 to -3) days, during announcement date (-2 to +2) days and then after announcement date of M&A (+3 to +30) days. After the analysis and the test have been conducted, results reveal that there is no significant Average Abnormal Return to shareholders on the announcement day (day zero) which is positive at 0.32%, while the result of Cumulative Abnormal Return is 18.19% and it is statistically significant at 10% level around the announcement day (a five day event window). Based on hypothesis testing, this study supported that the hypothesis is rejected since cumulative abnormal return is significant at 10% level